Using meteorological data to determine the risk of heat stress - Sleger, V.(Ceska Zemedelska Univ., Prague (Czech Republic). Technicka Fakulta) E-mail:sleger@tf. czu.cz; Neuberger, P.(Ceska Zemedelska Univ., Prague (Czech Republic). Technicka Fakulta) (Research in Agricultural Engineering (Praha), 2006)
A mathematical model of thermodynamic changes in the moist air inside a stable was designed using a computer program called MathCAD. Calculations of air temperature and humidity were carried out in poultry houses with layer hens. They were based on outdoor air characteristics and hens' biological production. Meteorological data were monitored hourly from May to August during the years 2000 to 2002. The calculated values were used to assess the potential of evaporation cooling in mild climatic conditions. The model may also be used to calculate the time the animals spend at a certain temperature before it is lowered by cooling. For example, in June 2002, the time the animals were exposed to 27 deg C was reduced from 39 to 22 h, and in July, it was from 33 to 4 h.